Distance to HIV care and treatment adherence: Adjusting for socio-demographic and geographical heterogeneity. (November 2018) - Amram, O.; Shoveller, J.; Hogg, R.; Wang, L.; Sereda, P.; Barrios, R.; Montaner, J.; Lima, V.
Highlights: Participants residing closer to their first ever ART prescribing physician are more likely to be highly adherent to ART. Participants residing in rural areas have poorer health outcomes when compared to those residing in urban areas. Discrepancies in HIV treatment outcomes exist despite the fact that HIV treatment costs are born directly by government. Abstract: Distance to health services plays an important role in determining access to care and an individual's health. This study aims to examine the relationship between distance to antiretroviral therapy (ART) prescribing physician and adherence to HIV treatment in British Columbia, Canada. Only participants who provided highly accurate locational data for both place of residence and their physician were used in the analysis. Using logistic regression, a multivariable confounder model was created to assess the association between distance and adherence. A geographically weighted logistic regression was also performed to adjust for spatial dependency. There were 1528 participants in the analysis, for a median distance of 17.85km. The final model showed further away from ART prescribing physician had a higher chance of incomplete adherence to ART (adjusted odds ratio 1.31; 95% Confidence Interval 1.04–1.65). Mobile services could potentially increase adherence rates for population residing further away from their ART prescribing physician.